Assistive devices caregivers use and find helpful to manage problem behaviors of dementia - Gitlin, Laura N. (Gerontechnology, 2010)
PURPOSE: Use of assistive devices in caring for individuals with dementia has not been systematically examined, particularly as it concerns managing behavioral symptoms. We tested a nonpharmacologic intervention to manage behaviors that involved instructing families in effective communication techniques, simplifying tasks and the home environment and using assistive devices. This paper describes the assistive devices provided to families assigned to intervention, extent of use of issued devices, their perceived helpfulness, and cost. DESIGN AND METHODS: Following each treatment session, occupational therapists (OT) documented time spent training in the use of strategies to manage problem behaviors. For families receiving assistive devices, OTs asked caregivers after 4 months whether they continued to use the device (yes/no), and extent to which it helped manage the targeted problems (not at all, somewhat, very helpful). We also tracked the costs associated with ordering, delivering and installing devices. RESULTS: Of 272 caregiver-patient dyads enrolled in the original trial, 136 were randomized to the intervention group, of whom 63 received one or more assistive devices. Of 13 intervention sessions, an average of 4 (31%) involved discussing or training caregivers in using assistive devices. A total of 197 devices (3 per dyad) were issued of which 87.6% were reported in use at 4 months. Caregivers reported that overall, devices were somewhat to very helpful. Devices ranged in cost from US$4.80 to US$282.93 with an average cost per dyad of US$152.52(SD=US$102.70) which included the device, its ordering, delivery and installation.